Produksi Jagung Manis (Zea mays saccharata Sturt) Terhadap Berbagai Jarak Tanam dan Pemberian Bokashi - Zulfahmi, Reza; Aulia Putrantri, Desty; Adzania Lestari, Mustika (Mediagro: Jurnal Ilmu-ilmu Pertanian, 2025)
Sweet corn is a high-value horticultural commodity with steadily increasing market demand. This study aimed to evaluate the production of sweet corn under different plant spacing and bokashi application. The research was conducted at the Horticultural Experimental Garden of Politeknik Negeri Lampung from July to October 2024, using a two-factor Randomized Complete Block Design (RCBD) with three replications. The first factor was plant spacing, consisting of three levels: 100 cm × 20 cm (JT1), 80 cm × 20 cm (JT2), and 60 cm × 20 cm (JT3). The second factor was bokashi application, also consisting of three levels: no bokashi (B0), 2.5 kg/m² bokashi (B1), and 5.0 kg/m² bokashi (B2). The results indicated that planting distance had a significant effect on all observed parameters. Bokashi application significantly influenced all observed parameters except stem diameter and cob diameter. No significant interaction was observed between planting distance and bokashi application. The 80 cm × 20 cm planting distance produced the highest yield, reaching 14.25 tons/ha. Bokashi application improved plant growth and yield compared to the control. Keywords: Bokashi Biofertilier, Growth, Horticulture, Yield